2021
DOI: 10.1007/s11665-020-05414-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Building Orientation and Aging on Strength–Stiffness Performance of Additively Manufactured Maraging Steel

Abstract: The interaction between building orientation and heat treatment may change the strengthstiffness behavior of maraging steel manufactured by Powder Bed Fusion (PBF). Further investigations about the correlation of the fracture characteristics and microstructures with the measured properties are needed to improve the process findings. Thus, this study investigated the way an interaction between building orientation (0º, 45º, and 90º) and specimens condition (as-built and aged) may change the defects interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 27 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…While the hardness for the PBF-LB/M-built components is approximately at 345 MPa, post-processing improves this characteristic to about 550 MPa for the SAT specimen and to 570 MPa for the HIP specimen. While these experimental results indicate an improvement of the mechanical behaviour induced by the heat treatment, they simultaneously lead to a modification of the microstructure of the material [71]. The microstructure of the as-built specimens is unidirectional and dominated by a very fine-grain structure (Figure 11).…”
Section: Static Testingmentioning
confidence: 93%
“…While the hardness for the PBF-LB/M-built components is approximately at 345 MPa, post-processing improves this characteristic to about 550 MPa for the SAT specimen and to 570 MPa for the HIP specimen. While these experimental results indicate an improvement of the mechanical behaviour induced by the heat treatment, they simultaneously lead to a modification of the microstructure of the material [71]. The microstructure of the as-built specimens is unidirectional and dominated by a very fine-grain structure (Figure 11).…”
Section: Static Testingmentioning
confidence: 93%
“…The average circularity of the powder particles is 0.93, where a circularity of 1 indicates a perfect circle [25]. Laser parameters for the PBF-LB/ 18Ni300 specimens were determined in a previous study [26] and are summarised in Table 3.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…In fact, optimized processing parameters and high solidification rate can be reduce and avoid the diffusion phenomenon once the materials experience high temperatures during less times, and consequently, there is no time for the formation of fragile and undesirable intermetallic phases or other compounds [17]. Some studies have reported the use of Yb-fibre [18,19] and pulsed Nd: YAG lasers [20][21][22] to melt common powders such as stainless steel , WC and Co. Nd: YAG laser have a high potential on the improvement of the thermal control and accuracy due to the short-pulsed energy when compared with the common CO2 lasers. These pulsed lasers display shorter wavelength, higher absorption levels by most metals, narrow focus and improved control of heat diffusion phenomenon.…”
Section: Introductionmentioning
confidence: 99%